Identification of Literacy Teaching Methods in Georgian Methodological Literature - Maglakelidze, Elene ("Intercultural Dialogues" Transactions, 2021)
One of the main and key issues of language mastery is the study of literacy in this language. The issues of identification and classification of literacy teaching methods have always been in the center of attention in the Georgian methodological literature. All methods used in teaching Georgian literacy can be conditionally divided into three groups: a) synthetic (modern terms: ascending, phonetic), b) analytical (ascending), c) analytical-synthetic (descending-ascending, balanced).Observation of the learning process shows that the selection and effectiveness of the teaching method of the alphabet is primarily determined by the nature-structure of this language. Thus, blindly transcribing it blindly from another language is totally unjustified.